IgG4-related pleural disease in a patient with a history of unknown origin acute pancreatitis: a case report and review of the literature. Issue 6 (2nd November 2019) - Damas, F.; Ghysen, K.; Gester, F.; Heinen, V.; Duysinx, B.; Louis, R.; Guiot, J.
ABSTRACT: Immunoglobulin G4-related disease is a rare autoimmune systemic disease with the capability of involving every organ. The disease is microscopically defined by a diffuse tissular inflammation with an infiltration of IgG4 positive plasma cells in the affected organs. IgG4 disease has an increasing incidence in the last few years with a growing interest in its pathophysiology still misunderstood to date. Despite the growing recognition of this pathology, the literature still does not allow to propose a simple diagnostic algorithm. In this article, we present a case of a 56-year-old man with a history of unknown etiology acute pancreatitis and a unilateral pleural effusion.